(untitled) (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: Surgical correction of congenital meningo encephalocele in a new born Jersey calf. Materials and methods: A day old jersey calf was presented with a swelling over frontal region, whioch was diagnosed as congenital cranial meningocele by findings of clinical examination, radiography and the same was corrected surgically under local infiltration anesthesia using lignocaine hydrochloride. Results: Recurrence was not observed in the calf and it was recovered uneventfully Conclusion: Congenital defects should be attended as earlier as possible so as to increase the chance of survivability. http://doi.org/10.5455/javar.2016.c143